Induction and disappearance of γH2AX foci and formation of micronuclei after exposure of human lymphocytes to 60Co γ-rays and p(66)+ Be(40) neutrons. (February 2014) - Vandersickel, Veerle; Beukes, Philip; Van Bockstaele, Bram; Depuydt, Julie; Vral, Anne; Slabbert, Jacobus
Abstract Purpose: To investigate both the formation of micronuclei (MN) and the induction and subsequent loss of phosphorylated histone H2AX foci (γH2AX foci) after in vitro exposure of human lymphocytes to either 60Co γ-rays or p(66)+ Be(40) neutrons. Materials and methods: MN dose response (DR) curves were obtained by exposing isolated lymphocytes of 10 different donors to doses ranging from 0–4 Gy γ-rays or 0–2 Gy neutrons. Also, γH2AX foci DR curves were obtained following exposure to doses ranging from 0–0.5 Gy of either γ-rays or neutrons. Foci kinetics for lymphocytes for a single donor exposed to 0.5 Gy γ-rays or neutrons were studied up to 24 hours post-irradiation. Results: Micronuclei yields following neutron exposure were consistently higher compared to that from 60Co γ-rays. All MN yields were over-dispersed compared to a Poisson distribution. Over-dispersion was higher after neutron irradiation for all doses > 0.1 Gy. Up to 4 hours post-irradiation lower yields of neutron-induced γH2AX foci were observed. Between 4 and 24 hours the numbers of foci from neutrons were consistently higher than that from γ-rays. The half-live of foci disappearance is only marginally longer for neutrons compared to that from γ-rays. Foci formations were more likely to be over-dispersed for neutron irradiations. Conclusion: Although neutrons are more effective to induce MN, the absolute number of induced γH2AX foci are less at first compared to γ-rays. With time neutron-induced foci are more persistent. These findings are helpful for using γH2AX foci in biodosimetry and to understand the repair of neutron-induced cellular damage.